Islamic Republic of Mauritania : Staff Report for the 2003 Article IV Consultation, and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2003)
Mauritania successfully completed its previous poverty reduction growth facility arrangement in December 2002. The focus of this report is on the effectiveness of policies adopted in the last few years and the medium-term strategy. Macroeconomic stability under the IMF-supported program and the above structural reforms underpinned progress in reducing poverty and improving social indicators, and the development of the Poverty Reduction Strategy Paper (PRSP) was a major achievement. The banking system has remained highly concentrated with inadequate financial intermediation, and difficulties have persisted in the operations of the foreign exchange market.